The Effect of Dental Implant Drills Materials on Heat Generation in Osteotomy Sites: A Systematic Review - Chakraborty, Shreyasi; Moufti, Mohammad-Adel; Kheder, Waad (European Journal of Dentistry, 2023)
The aim of this review was to examine the impact of dental implant drill materials and wear profiles on heat generation in the osteotomy sites as reported in experimental studies and to critically appraise these studies. The research question was formulated based on predefined patient, intervention, comparison, and outcome (PICO) elements. A comprehensive electronic search was undertaken in Medline/PubMed Central, Science Direct, and Google Scholar, using predetermined keywords, followed by a manual search of the bibliography of the selected articles. The selection of the studies for the critical appraisal part of our study was based on the criteria used to assess the study designs such as study aims, outcome measure, clarity of method, sample selection, randomization, allocation concealment, sample attrition, bias, method of data analysis, and external validity. Increased heat generation was observed with both ceramic and metal drills; the heat generation was proportional to drills' wear. The literature was inconclusive regarding the association between drill material and heat generation. However, drill materials had a significant influence on the overall temperature increase during osteotomy. The noncoated drills showed a higher wear resistance, and it has been observed that using worn drills leads to more friction contact, reduced drill cutting efficiency, and increased heat generation. Eleven in vitro studies met the inclusion criteria, and showed a considerable methodological heterogeneity and confounding factors, including drill geometry, speed and load, depth and diameter, number of uses, irrigation protocol, study specimens, and the heat measuring device. Besides, most of the studies have a potential operator and assessor bias, and some have sponsorship bias. It is possible to conclude that the literature is not conclusive on the effect of drill materials on heat generation during osteotomy. Lack of standardization and uniformity in the study design, along with potential bias in the study methodology can be the reason for the heterogeneity of the results.
Keywords: ceramics; dental implant; drills; friction; heat; osteotomy